The Influence of The Quality of Interpersonal Relationships on Student Self-Concept - Dinda Almira Sahputri; Najwa Aurelia; Ajeng Dwi Larasati (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2023)
Interpersonal relationships are an important factor in the formation of one's self-concept. This research is a type of qualitative research with a literature review approach. The keywords used are